Forum shopping and forum selling in German patent litigation: A quantitative analysis - Sibylle H. Lehmann-Hasemeyer; Alexander Morell (Leibniz Institute for Financial Research SAFE, 2025)
Using data on all patent cases in front of German courts between 2010 and 2015 we find that plaintiffs in patentinfringement cases mainly chose the venue where to sue by the speed with which courts dispose of their cases. We also find that quality - measured, both, as the fraction of cases challenged in the next instance and the ratio of successful appeals in the year before filing - has an impact on court choice by patent plaintiffs. We can further show that plaintiffs merely shop between three German courts, namely Duesseldorf, Munich and Mannheim. Moreover, we find that once one of these three courts introduces an additional panel of three judges, thereby working faster, the other two courts increase their working speed, too. This indicates that, indeed, courts actively compete for cases. However, we do not find evidence for courts reacting to a competitor's increase in speed by deciding in the plaintiffs favor more often or by deteriorating quality of decisions. We thank the ministries of justice of the 16 German Laender for the detailed data on patent cases. Moreover, we thank Stefan Bechtold, Fabian Gaessler, Dietmar Harhoff, Lea Tochtermann, Mike Schuster, Holger Spamann, the participants of the network meeting of the DFG network "Conflict Strategies in Innovation Markets" in Mannheim (Dec. 2023), the participants of the International Meeting of Law and Economics in Bruges (Apr. 2024), seminar participants at the ETH Zurich (Apr. 2024), participants of the CELS 2024 at Emory Law School, Atlanta (Nov. 2024), and the participants of the SAFE 2025 research retreat (Jan. 2025) for their valuable comments.
Keywords: D23; K11; K41; O34; 330; Organizational Behavior; Intellectual Property; Litigation; Patents and Innovation